The Meaning of Academic Degrees for Madurese Society In Disruption - Musthafa, Fera Andriani Djakfar (International Conference on Islamic Studies, 2021)
In Madurese society, university graduates still have a position that is considered. It is proven by the fact that there are still many people who are interested in continuing their studies to university level. Of course the main reason is to seek knowledge, but it is undeniable that an academic degree is no less important. This article discusses several things including, what is the meaning of academic degrees in Madurese society? what is the ideal profile of a college graduate? From the characteristics of a college graduate, what aspects are most expected by society? This is a qualitative research by applying phenomenology to find the hidden meaning of a phenomenon. Data were collected from observations and interviews with several community leaders, representatives of the general public, and also college students. For the concept of phenomenology, researcher will refer to Alfred Schutz's thinking who built a theoretical bridge connecting science and subjectivity. He agreed with Weber's view that human actions become social relations when humans give certain meanings to their actions, and other people also understand their actions as meaningful. One of the offers of the consequences of the method that it is offered through an observation model, that is divided based on direct and indirect method. Technically, the observation method in collecting this data can be done by using a list of questions or an interview guide to obtain the results of self-observation of the respondent's actions. In addition, interviews can be conducted more flexibly in an informal way. This article found that academic degrees are considered important for the Madurese community, especially to facilitate careers and gain legitimacy in society. Meanwhile, the ideal profile of a college graduate is to have competence in the field of science, good performance, and good character. However, of these characteristics, the Madurese community most expects is a good character. On the other hand, if a graduate has a bad character then he is considered to have failed to practice his knowledge and is not appreciated in society.